INTENSIVE WAYS OF TEACHING TEENAGERS ENGLISH (Journal of Uzbekistan’s Development and Research, 2025)
modern programs in foreign languages contain materials focused both on the final product and on the learning process. The development of intensive methods for universities and schools remains an urgent task today. The article defines the tasks of the intensive method of teaching in the university and the main factors confirming the effectiveness of the intensive methods of teaching a foreign language.